Atuação profissional do bibliotecário em ambiente empresarial: a informação como insumo estratégico para tomada de decisão - ALVES, Geovana Potira Martins (2021)
To present the changes in the spaces of action of the librarian having as main focus the business area, exposing that due to the advancement of information technologies (ICTs) the professional's space of performance is expanding. Its general objective is to investigate how it would be possible for the librarian to act in an information unit in the business space, using information as a strategic input for decision making.In order to reach the objective, a bibliographic survey was carried out, addressing the training, performance and skills required for a good performance in business information units. A questionnaire was applied to a librarian working in an information unit that serves the industrial segment, in order to know the objectives of the information unit located in a business environment, as well as the relevance of the professional who works in it. In view of the research carried out, it is concluded that the professional needs to keep up-to-date with the technological advances to help companies access information through the work developed in the information units.